Dietary practices in treatment of Hypoglycaemia in elevated one-hour postload glucose and diabetes - Vindedzis, Sally Ann (Curtin University, 2014)
This thesis, presented as seven published papers, investigates the under-researched area of dietary practices in hypoglycaemia in diabetes and elevated postload glucose. Research findings address resolution of relative hypoglycaemia in elevated 1-h postload glucose. In hypoglycaemia in diabetes, findings address optimum dietary treatment, patterns of food selection, the association between followup carbohydrate and repeat hypoglycaemia, knowledge of alcohol-induced sustained hypoglycaemia, and identification, treatment, frequency and documentation of hypoglycaemia in nasogastric feeding on the general ward.